(untitled) (Global Journal of Medical Research, 2020)
To prevent hypertension, which is closely related to lifestyle, especially eating habits, it is necessary to reduce salt intake. Therefore, in this study, we performed a saltiness cognition threshold test for participants at the university festival and obtained the saltiness cognition threshold results for the general public. 94 % of participants could perceive salty taste when the salty taste concentration was 1.0 % or less. On the other hand, two participants could not perceive saltiness even at a salty concentration of 1.6%, a 67-year-old female, and an 82-yearold female. We would like to continue the saltiness cognition threshold test and collect the data of participants to clarify the saltiness cognition threshold for general people.